El realismo interno de Putnam en retrospectiva - Sankey, Howard (Analysis. Journal of Philosophical Research, 2018)
As is well known, Putnam changed his philosophical position on a number of occasionsthroughout his career. In this paper, I reconsider the position of internal realismwhich Putnam defended from the mid-1970’s until around 1990. The paper openswith a discussion of the position that Putnam called “metaphysical realism”, sincehis internal realism emerged out of a critique of that position. The paper then brieflypresents the internal realist view as one which involves an epistemic conception oftruth, as well as an anti-realist metaphysical outlook on which objects depend onconceptual scheme. The paper then provides a survey of the key objections to internalrealism which emerged in the ensuing debate with defenders of realism. The paperconcludes with a brief consideration of the relevance of Putnam’s later adoption ofa direct realist theory of perception with respect to the issue of realism.